Diaspora Economics - Tony Fang; Alex Wells (Institute of Labor Economics (IZA), 2022)
Diasporas are global communities of migrants who retain a sense of connection with their homeland. The concept is ancient but has only recently become an important area of research in economics. Due to their unique transnational characteristics, diasporas can have significant influence over economic exchange in several ways. In this chapter, these economic implications are explored alongside the political involvement of diasporas. It is found that modern technological advancements in communication and transportation are emphasizing the importance of global connections, leading to diaspora populations gaining increased importance in areas such as international trade, foreign policy, and economic development. For many countries, remittances from their diaspora abroad are a key source of capital for development. Global talent mobility is also examined, including its impacts on brain drain, and the competing, more recently explored phenomenon of brain gain. There is evidence showing that members of diasporas are critical to the formation of international entrepreneurial and commercial networks, owing to their ability to help overcome linguistic or cultural barriers. Governments that are best able to effectively harness the economic potential of the diaspora are the biggest winners. Diasporasâ exteuro™ efforts to shape policy, both foreign and domestic, are prominent in modern research, and various examples are examined. Despite the wide body of research on diaspora economics, the subject is still recent and there are many avenues for future research.
Keywords: J61; J68; 330; economic and political impacts; international migration; diaspora